Effects of Service Quality on Students’ Satisfaction in Libraries in Kenya Using Servperf Model: Case of St Pauls’ University in Kenya - Kandie, Hilary Kipchirchir (Archives of Business Research, 2018)
Service quality is increasingly recognized as being of key strategic value by organizations and more so in institutions of higher learning. These institutions are continuously seeking ways to offer quality service especially in the libraries. The purpose of this research study was to examine the effects of service quality on students’ satisfaction in libraries in Kenya, using Servperf Model. The objectives of the study were to determine the effect of service reliability on student’s satisfaction in libraries in Kenya; to examine the effect of service assurance on student’s satisfaction in libraries in Kenya; to establish the effect of service tangibility on student’s satisfaction in libraries in Kenya; and to determine the effect of service responsiveness on student’s satisfaction in libraries in Kenya. The study adopted a descriptive research design. The study targeted approximately 600 Bachelors degree students in the main campus. The sample size was 60 students who were picked through simple random sampling. The study collected primary data use of a questionnaire. A pilot test was conducted to test for validity and reliability of the data collection tool. The researcher personally administered the questionnaire to the respondents. The data collected from the field was cleaned, coded and entered in SPSS software which also aided in its analysis. The data was analysed through descriptive statistics which included frequency distribution tables, mean and standard deviation. The analysed data was presented using tables, charts and graphs. The study found out that the students felt secure and relaxed when interacting with the library staff and that the library was opened for students’ access at the appropriate time. The study also found out that the students had confidence in librarians’ ability in handling their problems. The librarians were always willing to help the library students and that the library staff had respect for all class of students. The study found out that the librarians were always available to respond to students’ needs and that they were competent in solving students problems. The library had functional facilities that inspired study and learning and that it had most e-resources the students needed for my studies. However, the students were not able to access the electronic resources in the library from home/ office. The study concludes that service reliability, service assurance, service tangibility and service responsiveness in the university library influenced students’ satisfaction to a great extent. The study recommends that the librarians should be well trained on quality aspects and service delivery so as to enhance service quality in the library. The study also recommends that libraries should be well equipped with modern functional facilities that inspire study and learning. The libraries should enhance proper recording and maintenance of the students’ details to create a better service responsiveness.